Ensuring 'appropriate' protections for young suspects - Hodgson, Jacqueline; Kemp, Vicky (Intersentia, 2015)
The book is the result of the first part of the European Commission funded research project 'Protecting young suspects in interrogations: a study on safeguards and best practice'. The legal study underlying this volume consisted of comparative research into existing procedural safeguards for juvenile suspects during interrogation in the legal frameworks of five selected Member States of the European Union: Belgium, England and Wales, Italy, Poland and the Netherlands. In Chapter 3 are presented the comparative # findings in relation to England and Wales.